Intervensi Dukungan Emosional dan Konseling Perawat untuk Menurunkan Beban Psikologis Pasien Infertil yang Mengikuti Program Bayi Tabung - Anisah Anisah; Imami Nur Rachmawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to collect, evaluate, and synthesize evidence of various emotional and psychological support interventions in reducing the psychological burden of infertile patients following the IVF program. This research method is a systematic review using Pubmed, Scopus, Science Direct, Google Scholar, CINAHL, EBSCOhost, and Proquest database searches. The study's results indicate several emotional and psychosocial support interventions carried out by several researchers abroad that aim to reduce the psychological burden of infertile patients undergoing an IVF program. In conclusion, this intervention combination effectively reduces the psychological and emotional burden of infertile patients undergoing IVF programs. In addition, it can also improve marital relations and partner intimacy to improve the quality of life of infertile couples. Keywords: Psychological Burden, Emotional Support, Infertility Patients, Psychological